2011
DOI: 10.2500/ajra.2011.25.3535
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thrombin in Chronic Rhinosinusitis–associated Tissue Remodeling

Abstract: The results of this study showed that there is increased activation of the coagulation system in the nasal mucosa of CRS patients and that thrombin may play a role in nasal polyp formation by stimulating VEGF production from airway epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 41 publications
2
62
2
1
Order By: Relevance
“…If NP formation is due to excessive fibrin deposition caused by down-regulation of t-PA, it may be feasible to diminish NP formation by administration of t-PA or activators of t-PA or administration of inhibitors of fibrinogenesis. Although in this study we did not assess the coagulation status in NPs, a recent study demonstrated that thrombin, a central component of the coagulation cascade, was up-regulated in NPs (42). Thus, the coagulation cascade might be involved in excessive fibrin deposition in NPs, interacting with the reduced fibrinolytic properties of the tissue that we describe herein.…”
Section: Discussionmentioning
confidence: 82%
“…If NP formation is due to excessive fibrin deposition caused by down-regulation of t-PA, it may be feasible to diminish NP formation by administration of t-PA or activators of t-PA or administration of inhibitors of fibrinogenesis. Although in this study we did not assess the coagulation status in NPs, a recent study demonstrated that thrombin, a central component of the coagulation cascade, was up-regulated in NPs (42). Thus, the coagulation cascade might be involved in excessive fibrin deposition in NPs, interacting with the reduced fibrinolytic properties of the tissue that we describe herein.…”
Section: Discussionmentioning
confidence: 82%
“…48 A role for PAI-1 is consistent, with recent observations regarding the expression of PAI-1 and thrombotic/fibrinolytic pathways in patients with CS. 49,50 The 4G allele of this gene has been linked to the regulation of fibrosis in asthmatic patients and in particular to airway remodeling leading to irreversible obstruction. 51 In our study the 4G allele was overrepresented in the NES group compared with the control group of subjects without sinus disease (0.53 vs 0.45).…”
Section: Noneosinophilic Sinusitismentioning
confidence: 99%
“…The tissue concentrations of transforming growth factor beta 1 (TGF-β1) were found correlated with plasminogen activator inhibitor-1 (PAI-1) in CRSsNP, and ECP correlated with urokinase-type plasminogen activator receptor (uPAR) protein in CRSwNP [19]. Exposure to thrombin and protease activator receptor-1 (PAR-1) agonist peptide increases significantly vascular endothelial growth factor (VEGF) production from cultured human airway epithelial cells [20].…”
Section: Coagulation Factorsmentioning
confidence: 96%
“…Finally, thrombin and thrombin-antithrombin (TAT) complexes were found significantly increased in nasal secretions of patients with CRSwNP with asthma compared with the control group [20].…”
Section: Coagulation Factorsmentioning
confidence: 99%